Dynamics of Bacterial and Fungal Communities and Metabolites During Aerobic Exposure in Whole-Plant Corn Silages With Two Different Moisture Levels - Bai, Chunsheng; Wang, Chao; Sun, Lin; Xu, Haiwen; Jiang, Yun; Na, Na; Yin, Guomei; Liu, Sibo; Xue, Yanlin (Frontiers in Microbiology, 2021)
The present study investigated the effect of high- and low-moisture content on bacterial and fungal communities, metabolites and fermentation quality in whole-plant corn silages during aerobic exposure. Corn plants with high- and low-moisture (380 and 320 g/kg, respectively) were harvested at one-third and two-thirds milk-line stages, respectively, ensiled in laboratory-scale silos, and then sampled at 350 days after ensiling and at 2- and 5-day after opening to investigate bacterial and fungal communities, metabolites and aerobic stability. High-moisture increased aerobic stability and pH, and decreased lactic acid and microbial counts in silages (P < 0.05). During aerobic exposure, the high-moisture silages had higher pH and lactic acid bacterial count than the high-moisture silages (P < 0.05); Acinetobacter sp. was the most main bacterial species in the silages; Candida glabrata and unclassified Candida had an increasing abundance and negatively correlation with aerobic stability of high-moisture silages (P < 0.05), while C. glabrata, Candida xylopsoci, unclassified Saccharomycetaceae, and unclassified Saccharomycetales negative correlated with aerobic stability of low-moisture silages (P < 0.05) with a rising Saccharomycetaceae; the silages had a reducing concentration of total metabolites (P < 0.05). Moreover, the high-moisture silages contained greater total metabolites, saturated fatty acids (palmitic and stearic acid), essential fatty acids (linoleic acid), essential amino acids (phenylalanine) and nonessential amino acids (alanine, beta-alanine and asparagine) than the low-moisture silages at 5 days of opening (P < 0.05). Thus, the high-moisture content improved the fermentation quality and aerobic stability. Acinetobacter sp. and Candida sp. dominated the bacterial and fungal communities, respectively; Candida sp. resulted in the aerobic deterioration in high-moisture silages, while the combined activities of Candida sp. and Saccharomycetaceae sp. caused the aerobic deterioration in low-moisture silages. The greater aerobic stability contributed to preserve the palmitic acid, stearic acid, linoleic acid, phenylalanine, alanine, beta-alanine and asparagine during aerobic exposure.